Molecular characteristics of mcr-1-carrying plasmids and new mcr-1 variant recovered from polyclonal clinical Escherichia coli from Argentina and Canada - Tijet, Nathalie (2017)
Tijet N. and Faccone D. contributed equally to this work.We have characterized nine mcr-1-harboring plasmids from clinical Escherichia coli isolatespreviously described in Argentina and Canada. Three of these plasmids carried a mcr-1-variantcalled here mcr-1.5. All these E. coli isolates were not clonally related and were recoveredin different years and locations. However, their mcr-1-harboring plasmids showed highidentity among them and to others characterized in other countries, which strongly suggeststhat this plasmid-type is playing an important role in spreading this mechanism of resistanceto polymyxins.